Quest for Identity in V.S. Naipaul’s Half a Life - Chauhan, Shweta (International Journal of Psychosocial Rehabilitation, 2020)
The present paper is an attempt to study V.S Naipaul’s Half a Life in the light of diasporic issues of exile and identity. V.S Naipaul’s characters are dispossessed immigrants eternally searching for roots and belongingness in a world of multiple cultures where in their very identity is threatened. His immigrants such as Mr. Biswas in A House for Mr. Biswas, Willie in Half a Life, Salim in A Bend in the River are chronically dispossessed expatriates. Their attempts to look for a fixed identity and home fall flat every time. V.S Naipaul’s world is a bleak one where there is no hope for any stability. He represents his own displacement from Trinidad to England, however, his ancestral roots lie in India.